Isolation of Steviol Glycosides from the Mixtures of S.Rebaudiana Stems and Leaves Using Ethanol and Ultrasound Technique - Zulkarnain, Jema'at (2013)
The mixture of s.rebaudiana stems and leaves will be extracted to get the stevioside. Stevioside is a diterpene steviol Glycoside which is produced by conventional process. It is used to sweeten soft drink,soya sauce, yoghurt and other food. It also good for diabetic patients. This research objective is to extract the steviol glycosides from the mixture of s.rebaudiana stems and leaves using ultrasound extraction technique and find their applications. The process normally include the extraction, pre-treatment, separation, purification and refining. These processes will use ultrasound technique and followed by High performance liquid chromatography analysis (HPLC). Ultrasound extraction technique is one of the techniques to extract the mixture of s.rebaudiana stems and leaves before the sample of the the mixture of s.rebaudiana stems and leaves is analyzed by HPLC. The mixture of s.rebaudiana stems and leaves will be in dry and powder condition before it extracted by ultrasound extraction technique using ethanol as a solvent. Power level that used in the extraction is 280 W and the time range is between 10min to 50min at temperature range of 200C to 600C. After that the analysis was performed using High performance liquid chromatography (HPLC). Using 30 min, 40 0C and 80% ethanol is the most suitable time, temperature and percent of solvent used to break the analyte and matrix bond and produce the steviol Glycoside in optimum yields. From this research we know that ultrasound extraction technique is most common technique and most suitable in order to extract the steviol glycosides from the mixture of s.rebaudiana stems and leaves. The optimum yield can afforded at extraction time of 30 minutes, extraction temperature of 40 0C and the percentage of ethanol of 80%. Extraction kinetic of steviol glycosides approved the second-order kinetic yielding good R2 values of 0.992.